PENINGKATAN HASIL BELAJAR TEMA CITA-CITAKU BERBASIS CONSTEKTUAL TEACHING LEARNING (CTL) DI KELAS IV SD NEGERI 1 GERGUNUNG - Sri Suwartini; Putri Zudhah Ferryka (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
This research is motivated by the fact that some students still experience learning difficulties in understanding the material which results in planned learning time being hampered, especially in the learning of the theme 'My dreams'. The teacher considers that in the theme module '' My Citizens '' the material is not enough to be understood by students because some of the material in the book does not explain in detail. The research method used is action research by determining the steps: planning, action, observation, and reflection in each step using two cycles. The results of the study from the first cycle were only 76.57% or 19 students who scored above the minimum completeness criteria while 23.43% or 11 students scored below the minimum completeness criteria. Because it has not yet reached the minimum completeness criteria, the researchers proceed to cycle II. In the second cycle there was a significant increase of 86.4% of students who have mastered the competencies that have been set. Of the total 30 students, 25 students have met the specified minimum completeness criteria. From the results of the implementation of cycle I and cycle II, it can be concluded that using the contextual teaching learning method can improve the learning outcomes of the theme